2019
DOI: 10.3233/jad-190369
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Benefits of Edaravone for Alzheimer’s Disease with Chronic Cerebral Hypoperfusion in a Novel Mouse Model

Abstract: Alzheimer's disease (AD) and chronic cerebral hypoperfusion (CCH) often coexist in dementia patients in aging societies. The hallmarks of AD including amyloid-β (Aβ)/phosphorylated tau (pTau) and pathology-related events such as neural oxidative stress and neuroinflammation play critical roles in pathogenesis of AD with CCH. A large number of lessons from failures of drugs targeting a single target or pathway on this so complicated disease indicate that disease-modifying therapies targeting multiple key pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 41 publications
3
12
0
1
Order By: Relevance
“…Clinically, increased white matter grades measured using Fazekas's grading scale are positively correlated with cognitive decline (37). The results of this study are in agreement with those of previous studies (35,36).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Clinically, increased white matter grades measured using Fazekas's grading scale are positively correlated with cognitive decline (37). The results of this study are in agreement with those of previous studies (35,36).…”
Section: Discussionsupporting
confidence: 91%
“…The corpus callosum consists of white matter supplied with arterial blood from branches of the internal carotid artery and middle cerebral artery that are not immediately or entirely compensated by redistribution of collateral circulation (34). The accentuated vulnerability of the corpus callosum in ischemia-related white matter damage has been implicated in cognitive impairment and imbalance (35,36). Clinically, increased white matter grades measured using Fazekas's grading scale are positively correlated with cognitive decline (37).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the Alzheimer's Disease Neuroimaging Initiative public database revealed that Pittsburg compound B (PIB) positivity increased total WMH volume independently of the predicted AD diagnosis, that those diagnosed as having AD had greater WMH volume among PIB-positive subjects than normal control subjects and that both WMH and PIB status at the baseline conferred risk for future diagnosis of AD, suggesting that WMH contributes to the presentation of AD and may provide a second hit necessary for the clinical manifestation of the disease [84]. We revealed that neural oxidative stress and neuroinflammation were enhanced in AD model mice with CCH and that edaravone, a free radical scavenger, significantly improved motor and cognitive deficits, attenuated neuronal loss, reduced Aβ/phosphorylated tau (pTau) accumulation and alleviated neural oxidative stress and neuroinflammation in the AD mouse model with CCH [85]. Additionally, CCH greatly enhanced the number of Aβ oligomer-positive/pTau cells, the expression of peroxidation products (4-HNE and 8-OHdG), mitochondrial fission proteins (Drp1 and Fis1), and decreased the expression of mitochondrial fusion proteins (Opa1 and Mfn1) in the CTX and thalamus (TH) of AD model mice at 12 month of age, demonstrating that CCH shifted the balance in mitochondrial morphology from fusion to fission [86].…”
Section: Chronic Cerebral Hypoperfusionmentioning
confidence: 90%
“…Therefore, direct comparison of such measurement between CSF and serum should be performed in future. In addition, these findings warrant future studies to see whether antioxidant intervention might help preventing progression of neurodegenerative diseases including AD 7,11,100 …”
Section: Csf Oxidative Stress Markers In Ad In Vivomentioning
confidence: 99%
“…In fact, edaravone, a free radical scavenger, is clinically being available to ameliorate stroke and ALS, in both of which oxidative stress actively participates in the pathogenesis and progression of the diseases 6 . This drug has also been tested in the mouse model of AD 7 …”
Section: Role Of Oxidative Stress In Admentioning
confidence: 99%